The Life of Thomas Telford, Civil Engineer With an Introductory History of Roads and Travelling in Great Britain - Smiles, Samuel 1812-1904 (Cambridge University Press, 1867)
This biography of the civil engineer Thomas Telford (1757-1834) was published in 1867 by Samuel Smiles (1812-1904), the author of Self-Help and of other biographies of engineers and innovators. Smiles had already written about Telford's life and achievements in Volume 2 of his Lives of the Engineers (which is also reissued in this series), but in returning to the topic he adds to this new edition an introductory section (taken from Volume 1 of Lives of the Engineers) on the history of roads in Britain, from prehistoric trackways, via the Romans, to the modern road-building system pioneered by John Metcalf (the extraordinary 'Blind Jack of Knaresborough') and Telford himself. This illustrated work gives engaging accounts from earlier writers of the perils of road travel, and also deals in detail with Telford's own career as a builder of roads, bridges and canals.